Тебя убьют первым: роман / Анна и Сергей Литвиновы - Литвинова Анна Витальевна (Эксмо, 2020)
Экземпляры: ЦБ (20210318) / Инвентарный номер: 53472 / Цена: 340.00 / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: Л 64 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44